Career choices and pathways determinants among graduate nurses in low and medium-income countries: a case study of Pwani University Kenya - Omwenga, Samwel Nyamweya (Jooust, 2023)
The existing shortage in human resources for health (HRH) remains a global concern, making healthcare workers a global priority. While nurses comprise a significant component of HRH, their shortages, especially in low- and middle-income countries (LMICs), have greatly contributed to the persistent poor health outcomes and poor progress towards attaining universal health coverage. Moreover, universal health coverage largely depends on attracting and retaining nurses in primary health care (PHC). However, there is very limited understanding of the factors that influence graduate nurses‘ decisions when choosing a career path in nursing after training, especially in LMICs. Furthermore, current research has shown a worrying increase in the attrition rate of graduate nurses, indicating that more than half of these nurses intend to leave nursing practice within their first year of employment. Therefore, understanding how these graduate nurses decide on their career path is critical in informing future policies on attraction and retention in PHC. This thesis paper explores the factors influencing career choices and pathways of graduate nurses in low- and middle-income countries and their implication in the attraction and retention of graduate nurses in primary health care. A systematic literature review was conducted to examine the factors influencing career choices and pathways of graduate nurses in LMICs. An empirical study established graduate nurses' career choices and pathways trained at Pwani University, Kenya. Quantitative and qualitative data collection involved an online self-administered questionnaire followed by individual in-depth interviews of selected participants to better understand the experiences behind their career choices. From the study, there was a significant statistical relationship between respondents‘ university entry status and current job (p= 0.02) whereby majority of those who had direct entry were in private sector (42%) while majority of those who upgraded were in public sector (24%). The study results show that mentorship (58.9%) and parental influence (33.9%) were significant factors that influence career choices. Other factors that motivate individuals to choose nursing included the love of the physical nature of the profession, a desire to be part of a noble profession, exposure to caregiving, relatives in the nursing profession, and previous experiences with illness. Nurses are more likely to remain in their jobs if working conditions are favorable and if personal development opportunities are available. However, they are more likely to leave if there is a lack of growth opportunities, role ambiguity, a hostile environment, or more attractive external job opportunities. The study also showed that most nurses work in hospital services and prefer urban locations due to the availability of personal growth opportunities and job prospects. The study therefore recommends offering job security, personal growth opportunities, a supportive work environment, clear job roles, and incentives for nurses working in rural and remote areas to increase nurse attraction and retention in public healthcare. The current study further recommends a longer cohort follow-up study to be conducted, incorporating larger sample sizes from various settings to compare pertinent influencing factors among these groups.
Keywords: Career choices and pathways; Career choices and pathways among graduate nurses in low and medium-income countries; Career choices and pathways determinants among graduate nurses in low and medium-income, Kenya